Impact of trailing edge overhang length on the loss characteristics of fully cooled transonic nozzle guide vanes - Burdett, D; Povey, T (ASME International, 2022)
The trailing edge (TE) design of a cooled high-pressure (HP) nozzle guide vane (NGV) requires consideration of both cooling and aerodynamic performances. Two designs are in common use: the centered-ejection design, in which coolant is ejected through a slot in the TE with roughly symmetrical suction-side (SS) and pressure-side (PS) TE tips; and the SS-overhang design, in which the SS and PS TE tips are staggered. This second design has been favored in recent years because it has been presumed to be aerodynamically advantageous. In this article, we re-examine this assumption by studying a parametric design set between these two design extremes. We do this using extensive high-fidelity experimental measurements performed at engine-scaled conditions (matched Mach number, Reynolds number, and coolant-to-mainstream pressure ratio) on a full-annular cascade of real engine parts. To provide insight into the mechanisms affecting loss, we use complementary unsteady computational fluid dynamics (CFD) simulations. We analyze the changes in the flow structure, local loss coefficient distribution, wake mixing rate, average profile loss coefficient, and base pressures.